Yarning about pain: Evaluating communication training for health professionals at persistent pain services in Queensland, Australia. Issue 3 (June 2023) - Bernardes, Christina M; Ekberg, Stuart; Birch, Stephen; Claus, Andrew; Bryant, Matthew; Meuter, Renata; Isua, Jermaine; Gray, Paul; Kluver, Joseph P; Malacova, Eva; Jones, Corey; Houkamau, Kushla; et al.
Background: Providing cultural education to health professionals is essential in improving the quality of care and outcomes for Aboriginal and Torres Strait Islander patients. This study reports the evaluation of a novel training workshop used as an intervention to improve communication with Aboriginal and Torres Strait Islander patients of persistent pain services. Methods: In this single-arm intervention study, health professionals undertook a one-day workshop, which included cultural capability and communication skills training based on a clinical yarning framework. The workshop was delivered across three adult persistent pain clinics in Queensland. At the end of the training, participants completed a retrospective pre/post evaluation questionnaire (5 points Likert scale, 1 = very low to 5 = very high), to rate their perceived importance of communication training, their knowledge, ability and confidence to communicate effectively. Participants also rated their satisfaction with the training and suggested improvements for future trainings. Results: Fifty-seven health professionals were trained ( N = 57/111; 51% participation rate), 51 completed an evaluation questionnaire ( n = 51/57; 90% response rate). Significant improvements in the perceived importance of communication training, knowledge, ability and confidence to effectively communicate with Aboriginal and Torres Strait Islander patients were identified ( p < 0.001 ). The greatest increase was in the perceived confidence pre-training mean of 2.96 (SE = 0.11) to the post-training mean of 4.02 (SE = 0.09). Conclusion: This patient-centred communication training, delivered through a novel model that combines cultural capability and the clinical yarning framework applied to the pain management setting, was highly acceptable and significantly improved participants' perceived competence. This method is transferrable to other health system sectors seeking to train their clinical workforce with culturally sensitive communication skills.